Digitalisasi Tari Guel: Inovasi Kolaboratif Bersama Sanggar Genali Menuju Sanggar Mandiri dan Berdaya Saing: Pengabdian - Permata, Magfiah Murni Bintang; Setiawan, Indra; Sari, Dian Permata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of digital technology and changes in cultural consumption patterns have made traditional performing arts face significant challenges. Guel Dance, a Gayo cultural heritage, is also under pressure due to a lack of documentation, limited promotion, and low digital literacy among rural arts communities. This community service activity aims to digitize Guel Dance through audio-visual documentation, digital publication, and capacity building at the Genali Studio. The program, which took place from November 11–15, 2025, included initial discussions, task allocation, digitalization training, the complete and collaborative recording of Guel Dance with Munalo Dance, and the development and documentation of new costumes. The results show that digitalization not only strengthens cultural preservation but also opens up creative economic opportunities, expands public reach, and increases the studio's independence and competitiveness. Amid globalization and technological advances, traditional performing arts are increasingly under pressure from changing cultural consumption patterns. Guel Dance is also threatened by the shift in interest of the younger generation towards digital entertainment. Therefore, a digitalization program is crucial to bridge tradition with the demands of the digital era. Through digital media, Guel Dance can be well documented, promoted innovatively, and increase its economic value, strengthen cultural identity, and encourage cross-generational interaction.